Inflammatory Bowel Disease and Parkinson's Disease: A Nationwide Swedish Cohort Study. Issue 1 (16th May 2018) - Weimers, Petra; Halfvarson, Jonas; Sachs, Michael C; Saunders-Pullman, Rachel; Ludvigsson, Jonas F; Peter, Inga; Burisch, Johan; Olén, Ola
Abstract: Background: Few studies have examined the association between inflammatory bowel disease (IBD) and Parkinson's disease (PD). Methods: To estimate the incidence and relative risk of PD development in a cohort of adult IBD, we included all incident IBD patients (n = 39, 652) in the Swedish National Patient Register (NPR) between 2002 and 2014 (ulcerative colitis [UC]: n = 24, 422; Crohn's disease [CD]: n = 11, 418; IBD-unclassified [IBD-U]: n = 3812). Each IBD patient was matched for sex, age, year, and place of residence with up to 10 reference individuals (n = 396, 520). In a cohort design, all incident PD occurring after the index date was included from the NPR. In a case-control design, all incident PD occurring before the index date was included. The association between IBD and PD and vice versa was investigated by multivariable Cox and logistic regression. Results: In IBD, there were 103 cases of incident PD, resulting in hazard ratios (HRs) for PD of 1.3 (95% confidence interval [CI], 1.0–1.7; P = 0.04) in UC, 1.1 (95% CI, 0.7–1.7) in CD, and 1.7 (95% CI, 0.8–3.0) in IBD-U. However, these effects disappeared when adjusting for number of medical visits during follow-up to minimize potential surveillance bias. In a case-control analysis, IBD patients were more likely to have prevalent PD at the time of IBD diagnosis than matched controls, with odds ratios of 1.4 (95% CI, 1.2–1.8) in all IBD patients, 1.4 (95% CI, 1.1–1.9) for UC, and 1.6 (95% CI, 1.1–2.3) for CD patients alone. Conclusions: IBD is associated with an increased risk of PD, but some of this association might be explained by surveillance bias.